Fifteen years of epidemiologic, virologic and syndromic influenza surveillance: A focus on type B virus and the effects of vaccine mismatch in Liguria region, Italy - Cecilia Trucchi; Cristiano Alicino; Andrea Orsi; Chiara Paganino; Ilaria Barberis; Federico Grammatico; Paola Canepa; Emanuela Rappazzo; Bianca Bruzzone; Laura Sticchi; Filippo Ansaldi (Taylor & Francis Group, 2017)
In order to estimate the burden of influenza and to describe the genetic evolutionary pattern and antigenic variability of type B viral strains, data deriving from 3 surveillance systems active in Liguria region, Northern Italy, were described. Since the re-emergence of the Victoria lineage in 2001, the clinical-epidemiological and syndromic surveillances demonstrated the heavy burden of influenza like illness (ILI) syndrome. Focusing on type B influenza virus, it predominated or played a relevant epidemic role in the 50% of the evaluated influenza seasons. Furthermore, the virologic surveillance demonstrated the frequent co-circulation of both lineages an heterogeneous circulation of different influenza B strains, determining a partial or complete mismatch in at least 6 influenza seasons. The undemonstrated cross-reactivity between lineages and the unpredictability of predominant lineage arose the scientific debate about the opportunity to include the quadrivalent influenza vaccine among the preventive tools to improve the protection against type B viruses. The integration of different surveillance systems highly contribute to estimate the poorly evaluated burden of type B influenza virus and help to find variants to include in the vaccine formulation.